Rapid and sensitive detection of Phytophthora colocasiae responsible for the taro leaf blight using conventional and real‐time PCR assay. Issue 2 (24th February 2014) - Nath, Vishnu S.; Hegde, Vinayaka M.; Jeeva, Muthulekshmi L.; Misra, Raj S.; Veena, Syamala S.; Raj, Mithun; Unnikrishnan, Suresh K.; Darveekaran, Sree S.
Abstract Conventional and real‐time PCR assays were developed for sensitive and specific detection of Phytophthora colocasiae, an oomycete pathogen that causes leaf blight and corm rot of taro. A set of three primer pairs was designed from regions of the RAS‐related protein (Ypt1), G protein alpha‐subunit (GPA1) and phospho‐ribosylanthranilate isomerase (TRP1) genes. In conventional PCR, the lower limit of detection was 50 pg DNA, whereas in real‐time PCR, the detection limit was 12.5 fg for the primer based on Ypt1 gene. The cycle threshold values were linearly correlated with the concentration of the target DNA (range of R2 = 0.911–0.999). All the primer sets were successful in detecting P. colocasie from naturally infected leaves and tubers of taro. Phytophthora colocasiae was detected from artificially infested samples after 18 and 15 h of postinoculation in conventional and real‐time PCR assay, respectively. The developed PCR assay proved to be a robust and reliable technique to detect P. colocasiae in taro planting material and for assessing the distribution of pathogen within fields, thus aid in mitigating taro leaf blight.